7q+8r-6r=

Simple and best practice solution for 7q+8r-6r= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7q+8r-6r= equation:


Simplifying
7q + 8r + -6r = 0

Combine like terms: 8r + -6r = 2r
7q + 2r = 0

Solving
7q + 2r = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2r' to each side of the equation.
7q + 2r + -2r = 0 + -2r

Combine like terms: 2r + -2r = 0
7q + 0 = 0 + -2r
7q = 0 + -2r
Remove the zero:
7q = -2r

Divide each side by '7'.
q = -0.2857142857r

Simplifying
q = -0.2857142857r

You can always share this solution

See similar equations:

| 0.6666666y+5y=70-y | | 5x+2y=18 | | 4a+9a+2+4a= | | 2x-3y=11 | | 18=2(1g+4)+3(2g-6) | | 9+16x^2-24x=0 | | -4+6t-6= | | x-y=4v | | 3x+24=y | | 2n+4n-4n= | | 6(3.5+1r)-1=7r-r | | 10BC+7BC= | | 4t+7t+tu+8t= | | x=27 | | 8+1+9t= | | 5k+3k-4k= | | 8+7d= | | 3+k+7k= | | 1+2t= | | 4s+st= | | 4d+6d-7d= | | 5(x+2)=3x+7 | | -212b=-424 | | 8h-2h+10h= | | 7s+2=5-3s | | 6p-p= | | 4r-1=7 | | 2z+3yz-6z+2yz+y-z-4y= | | 5r-3r+7r= | | 3k-3k+8k+8km= | | 4x+27=x-3 | | 10n+8p= | | 6t-3t= | | 6+2s+2(8s+8)= | | n+6n= | | 4+3x=x-6 | | 3(1+5x)+7= | | 2(-5a-6)= | | 7w+7w+6w+5+7w= | | 4s+6s+6s+7= | | -3c+14=-7 | | 2(3x+5)=5(2x-4)-4x | | 10-15+2x=30 | | 15x+3(2x-1)=10(2x-3) | | -7p+3p+-5p= | | 2x+10-15=30 | | 6v+1+8v-9+9+5v= | | x^2-2=6-2x | | h+9h= | | s+2(1+2s)+8s= | | 3u+4(1+7u)+8u= | | 7d-8=-7 | | a-5+9a= | | 6+3y-5= | | 6z+7z+5z+8z+7z+7z= | | 3x+2=5x-3 | | -30-10=x | | 6y^2+18+12=0 | | 9q+2q+q+8q+9q= | | 9(5y+6)+4y+7y= | | 8x+x+6x+9x= | | 12m+2=3 | | 8x-15=3x-6 | | 5x-6=-3 | | 6x+7=4x+19 |

Equations solver categories